Psychosocial aspects of diabetes in pregnancy - Kalra, Bharti; Balhara, Yatan Pal Singh; Kalra, Sanjay (Journal of Social Health and Diabetes, 2014)
Recent guidelines promote a patient-centered approach to the management of diabetes. The relevance of the bio-psychosocial model or holistic approach has also been explored in women′s health. Specifically, psychosocial and psychiatric morbidity has been appreciated and analyzed in pregnancy and the postpartum period. However, minimal attention has been focused on the psychosocial and social factors that impact pregnancy complicated by diabetes. This is even more surprising from a South Asian perspective, where deep-rooted sociocultural mores create a milieu that may not be very friendly to the antenatal woman with diabetes. This review discusses the psychosocial issues relevant in the context of pregnancy among diabetics. An approach to address these issues has also been highlighted.
Keywords: Diabetes mellitus; pregnancy; psychosocial issues